Impact of Bilateral Coordinated Movement on Manipulative Skill Competency in Elementary School Students - Jun Chen; Xiaozan Wang; Weiyun Chen (MDPI AG, 2021)
Background: Researchers have found that manipulative skill competency in childhood not only helps to improve physical activity participation but also helps adolescents learn specialized sports skills. This study aimed to examine the effects of an eight-week bilateral coordinated movement (BCM) intervention on manipulative skill competency in school-aged children. Methods: The participants were 314 fourth-grade students from two elementary schools in China. This study used a two-arm quasi-experimental research design. For one elementary school, two fourth-grade classes were assigned to the BCM group and another two fourth-grade classes were assigned to the control group. For the other elementary school, one fourth-grade class was assigned to the BCM group and another fourth-grade class to the control group. The students in the BCM group received an eight-week, two 40 min BCM lessons in soccer, and another eight-week, two 40-min BCM lessons in basketball. The control group received an eight-week two regular 40 min PE lessons in soccer and basketball, respectively. The students' manipulative skill competency in soccer and basketball skills were pre- and post-tested using the two PE metric assessment rubrics. Data were analyzed by means of descriptive statistics, independent sample t-tests, and ANCOVA and ANOVA repeated measures. Results: The results showed a significant main effect of time (pre-test vs. post-test) in soccer skills (F = 273.095, p < 0.001, η2 = 0.468) and in basketball skills (F = 74.619, p < 0.001, η2 = 0.193). Additionally, the results revealed a significant main effect of the group (BCM group vs. control group) in soccer skills (F = 37.532, p < 0.001, η2 = 0.108) and a marginal significant main effect of the groups in basketball skills (F = 3.619, p = 0.058, η2 = 0.011). Furthermore, there was a significant interaction effect between the time and the group in soccer skills (F = 37.532, p < 0.001, η2 = 0.108) and in basketball skills (F = 18.380, p < 0.001, η2 = 0.056). Conclusions: It was concluded that after participation in the eight-week, 16 40 min lessons of BCM, the fourth-grade students showed greater improvement in soccer and basketball dribbling, passing and receiving skills, compared to the control group.